URGENSI PENDIDIKAN WIRAUSAHA (ENTERPRENEUR) BAGI MAHASISWA - Febriyanto, Febriyanto (AS-SALAM, 2013)
Increasing of the rate of poverty, unemployment and imbalance of economyare the problem urgely to be handled. The competent human resources isa indicator of success of progressive country. A little of enterpreneur ina region, draws a low power to competition. To make a progress of goodcompetence, the joining teachers to be more active in giving motivation tobe enterpeneur for their students. The scholars after graduating neededto be more inovative and creative in the matter of developing theirself,so that it can be relied on being created the job vacancy in order to thegrowing of economy in region will be developed and the rate of povertywill be decreased.Keywords: human recourses, Enterpreneur, student